Gênese de solos coesos do leste maranhense: relação solo-paisagem - Dantas, Jussara Silva; Marques Júnior, José [UNESP]; Martins Filho, Marcílio Vieira [UNESP]; Resende, José Maria Do Amaral; Camargo, Livia Arantes [UNESP]; Barbosa, Ronny Sobreira (Sociedade Brasileira de Ciência do Solo, 2014)
The occurrence of cohesive soils in Brazil is predominantly related to sandy-clay sediments of the Barreiras Formation, which are geologically related to the sedimentary deposits of the Tertiary period (from Paleocene to Pliocene), which constitute the geomorphological unit of the Coastal Plains. The objective of this study was to identify the occurrence of cohesive soils in the eastern region of the state of Maranhão, Brazil, and assess their relationship to position in the landscape. The area under study is in the Typuana Farm, in the East Maranhão region, in Brejo, MA, at the geographical coordinates of 03° 36' S and 42° 52' W. The predominant vegetation of the area is Cerrado (tropical savanna), with diverse floristic composition. Three trenches were dug (depth profiles 1, 2, and 3), one in each area of study with distinct vegetation, for morphological, physical, chemical, and mineralogical characterization, and for morphological classification of the soils. Kaolinite was the predominant mineral in the cohesive layers, but its degree of crystallinity did not affect the variation in soil density (1.40 to 1.56 kg dm-3) and resistance to penetration (1.24 to 2.18 MPa). It was found that position in the landscape was essential for distinction of cohesive soils, and those established in a concave landform exhibited the highest expression of the cohesive character, which resulted in higher soil fertility and organic matter, reflecting the more exuberant vegetation of the Cerradão.

A ocorrência dos solos coesos no Brasil está relacionada dominantemente com os sedimentos argiloarenosos da Formação Barreiras, os quais estão geologicamente relacionados com os depósitos sedimentares do período Terciário, que constituem a unidade geomorfológica dos Tabuleiros Costeiros. Os objetivos deste trabalho foram identificar a ocorrência de solos coesos e estudar suas relações com a paisagem na região leste do Estado do Maranhão. A área do estudo localiza-se na Fazenda Typuana, região leste maranhense, no município de Brejo, MA, nas coordenadas geográficas de 03º 36' S e 42º 52' W. A vegetação predominante da área de estudo é do tipo Cerrado, com uma composição florística diversificada. Foram abertas três trincheiras, uma em cada área do estudo, com distintas formações vegetais para as caracterizações morfológica, física, química, mineralógica e a classificação taxonômica dos solos. A caulinita foi o mineral predominante nos horizontes coesos, porém seu grau de cristalinidade não influenciou na variação da densidade do solo (1,40 a 1,56 kg dm-3) e na resistência à penetração (1,24 a 2,18 MPa). Constatou-se que a posição da paisagem foi determinante para a distinção dos solos coesos, de modo que os desenvolvidos em pedoforma côncava apresentaram a maior expressão do caráter coeso e com maior status de fertilidade e matéria orgânica, refletindo na vegetação mais exuberante, caracterizada pelo Cerradão.
Genesis of cohesive soils of eastern Maranhão: soil-landscape relation
Keywords: pedogênese; Argissolos; Formação Barreiras; pedogenetic process; Argisol; Barreiras Formation